Visibility and (alt)metrics of the Croatian Open Access (OA) journals - Stojanovski, Jadranka (Septentrio Conference Series, 2014)
See video of the presentation. For a small research community from the so called scientific periphery it's important to publish in the well-established international journals as well as to make their papers published in local journals visible to the international audience. In this paper we present how the portal of the Croatian scientific journals HRCAK influence the visibility of more than 300 included Open Access (OA) journals. Longitudinal shifts in journal content and distribution among scientific disciplines are observed. Different kind of journal and article metrics have been analysed and compared for HRCAK OA journals indexed in Scopus and Web of Science databases, examining the effect of OA on usage and citations. The results of the continuous work with Croatian journal publishers, National board for scholarly publishing responsible for subsidizing journal editorials, and with the most popular bibliographic databases producers are presented. Some desirable directions for the future development of the scholarly publishing in Croatia are indicated.